The Mystery Of The Location Of The City Of Iram, The Atlantis Of Arabia - Muttaqin, Mohammad Izdiyan; Dardiri, Ahmad Dardiri (UI Scholars Hub, 2022)
This study aims to discuss the characteristics of the Land of the 'Ad whose country is usually called the Land of Iram, and opinions about the location of its existence. This research is a library study that takes information from various sources. The author reached the conclusion that there are 4 characteristics of the Land of the 'Ad mentioned in the Qur'an, among them are: 1) there is a desert in it, 2) it has high buildings and pillars, 3) the buildings are visible and can be seen by people around them, 4) there is spring in it. The author also reaches the conclusion, that there are several locations that are considered as the location of the City of Iram by scholars and researchers, including: 1) the desert between Alexandria and Damascus, 2) the desert between Oman and Hadromaut, 3) ar-Rub'u al- Khali, 4) A mountain in Sham called Al-Ahqaf, 5) Valley between Oman and Mahrah in Yemen 6) As-Shihr a desert in Yemen bordering the sea, 7) Desert of Dahna' Saudi Arabia, 8) Awwam Temple in Yemen region. And until now the exact location of the City of Iram is still a mystery. Keywords: People of 'Ad, Prophet Hud, City of Iram